Mobile-Based Integrated Management Application for Sick Toddlers at Puskesmas Sumalata - Makaweks, Yanes Theodora; Manaha, Cheisya Framita Lady; Laoh, Lidya Chitra (Jurnal Multidisiplin Madani, 2024)
Infant mortality is a critical public health indicator. Among other efforts to reduce this figure is the improved health skills of treating sick toddlers, and the Sumalata center was a of the centers located in the north Gorontalo district. There was a strategy in the Sumalata center for reducing toddler mortality, pain, and disability. People may employ apps to get information for counseling, immunization registration, and outpatient registration. Researchers used prototype methods beginning with the development phase of the communication process, data collection, quick plan design, modeling quick design identifying system needs, construction of the prototype of deployment delivery and feedback development on this stage, feedback from the puskesmas Sumalata. This system was designed with javascript as a programming language, alternative native as a user interface display on the front-end, nodejs, and mysql as a database on the back-end. The applications developed allow patients to enroll in immunization, register for clinical care, and obtain information from the Sumalata Medical Center